2022
DOI: 10.14245/ns.2244352.176
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Versus Conservative Management for Treating Unstable Atlas Fractures: A Multicenter Study

Abstract: Objective: This multicenter study compared radiological parameters and clinical outcomes between surgical and non-surgical management and investigated treatment characteristics associated with the successful management of unstable atlas fractures. Methods:We retrospectively evaluated 53 consecutive patients with unstable atlas fracture who underwent halo-vest immobilization (HVI) or surgical fixation. Clinical outcomes were assessed using neck visual analog scale and disability index. The radiological assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In the past, skull traction, external fixation of the Halo-vest head frame, and other non-surgical treatment methods were mostly used, but the treatment time was long, the patients were difficult to tolerate, and the clinical results were poor [ 5 , 6 ]. Therefore, for better fracture healing and restoration of stability in the occipitocervical junction, it has been suggested by a majority of surgeons that patients with unstable atlas fractures should undergo surgical treatment at an early stage [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, skull traction, external fixation of the Halo-vest head frame, and other non-surgical treatment methods were mostly used, but the treatment time was long, the patients were difficult to tolerate, and the clinical results were poor [ 5 , 6 ]. Therefore, for better fracture healing and restoration of stability in the occipitocervical junction, it has been suggested by a majority of surgeons that patients with unstable atlas fractures should undergo surgical treatment at an early stage [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ideal and comprehensive treatment should be changed according to modest concept.Based on these perspectives, the authors have reported clinical outcomes of multicenter comparative study between conservative and surgical management for isolated atlas fracture, which have a high potential for instability. 5 The authors have also evaluated preoperative radiological parameters that associated with faster osseous fusion and better clinical outcome after treatment in both groups. All patients enrolled in the study had atlas fracture with lateral mass displacement (LMD) following "rule of Spence" and disfunction of TAL including either type I or type II injury.…”
mentioning
confidence: 99%
“…Based on these perspectives, the authors have reported clinical outcomes of multicenter comparative study between conservative and surgical management for isolated atlas fracture, which have a high potential for instability [ 5 ]. The authors have also evaluated preoperative radiological parameters that associated with faster osseous fusion and better clinical outcome after treatment in both groups.…”
mentioning
confidence: 99%